2021
DOI: 10.18203/issn.2455-4510.intjresorthop20211436
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of management of intertrochanteric fracture by dynamic hip screw and proximal femoral nailing

Abstract: <p><strong>Background:</strong> The purpose of the present study is to verify the theoretical advantages of the intramedullary device over the dynamic hip screw devices and also whether it actually alters the eventual functional outcome of the patient.          </p><p><strong>Methods:</strong> The study is comparative prospective study in which 40 patients were taken and treated either with dynamic hip screw or proximal femoral nailing. The clinical data will be collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…9 Parsurampuriya VK et al found that the ratio of women: men range from 2:1 to 8:1 likely because of post-menopausal osteoporosis. 10 Singh K et al did final follow up of all 32 patients which were included in the study managed by PFN. Modified HHS was accessed at 4-6 weeks and 3-4 months and found to be 41.19 (SD =12.89) & 64.66 (SD =13.35) respectively.…”
Section: Resultsmentioning
confidence: 99%
“…9 Parsurampuriya VK et al found that the ratio of women: men range from 2:1 to 8:1 likely because of post-menopausal osteoporosis. 10 Singh K et al did final follow up of all 32 patients which were included in the study managed by PFN. Modified HHS was accessed at 4-6 weeks and 3-4 months and found to be 41.19 (SD =12.89) & 64.66 (SD =13.35) respectively.…”
Section: Resultsmentioning
confidence: 99%
“…On functional outcomes post intertrochanteric fracture of femur treated with different implants immense amount of literature is available (Zhang et al, 2014;Chen et al, 2021;Parsurampuriya et al, 2021;Prakash et al, 2022). But we have found none which discusses on reduction of fracture and the functional outcome.…”
Section: Medical Sciencementioning
confidence: 94%